Antimicrobial Activity and Mechanism of Inhibition of Silver Nanoparticles against Extreme Halophilic Archaea - Thombre, Rebecca S.; Shinde, Vinaya; Thaiparambil, Elvina; Zende, Samruddhi; Mehta, Sourabh (Frontiers in Microbiology, 2016)
Haloarchaea are salt-loving halophilic microorganism’s that inhabit marine environments, sea water, salterns, and lakes. The resistance of haloarchaea to physical extremities that challenge organismic survival is ubiquitous. Metal and antibiotic resistance of haloarchaea has been on an upsurge due to the exposure of these organisms to metal sinks and drug resistance genes augmented in their natural habitats due to anthropogenic activities and environmental pollution. The efficacy of silver nanoparticles (SNPs) as a potent and broad spectrum inhibitory agent is known however, there are no reports on the inhibitory activity of SNPs against haloarchaea. In the present study, we have investigated the antimicrobial potentials of SNPs synthesized using aqueous leaf extract of Cinnamomum tamala against antibiotic resistant haloarchaeal isolates Haloferax prahovense RR8, Haloferax lucentense RR15, Haloarcula argentinensis RR10 and Haloarcula tradensis RR13. The synthesized SNPs were characterized by UV-Vis spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, dynamic light scattering, X-ray diffraction and Fourier transform infrared spectroscopy. The SNPs demonstrated potent antimicrobial activity against the haloarchaea with a minimum inhibitory concentration of 300- 400µg/ml. Growth kinetics of haloarchaea in the presence of SNPs was studied by employing the Baranyi mathematical model for microbial growth using the DMFit curve fitting programme. The C. tamala SNPs also demonstrated cytotoxic activity against human lung adenocarcinoma epithelial cell line (A540) and human breast adenocarcinoma cell line (MCF-7). The mechanism of inhibition of haloarchaea by the SNPs was investigated. The plausible mechanism proposed is the alterations and disruption of haloarchaeal membrane permeability by turbulence, inhibition of respiratory dehydrogenases and lipid peroxidation causing cellular and DNA damage resulting in cell death.